Database systems for advanced applications : DASFAA 2018 International Workshops: BDMS, BDQM, GDMA, and SeCoP, Gold Coast, QLD, Australia, May 21-24, 2018, Proceedings /: DASFAA 2018 International Workshops: BDMS, BDQM, GDMA, and SeCoP, Gold Coast, QLD, Australia, May 21-24, 2018, Proceedings. (2018) - Unknown
No abstract available